ANALYSIS OF THE IMPACT OF PROFITABILITY, LEVERAGE AND FINANCIAL DISTRESS ON TAX AVOIDANCE IN FOOD & BEVERAGE COMPANIES ON THE IDX (2019-2023) - Riduwan Riduwan (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This research aims to analyze the influence of Profitability, Leverage, and Financial Distress on Tax Avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. This type of research uses statistics with a quantitative approach. The data collection technique employs the documentation method, which involves collecting data from financial reports published on the official IDX website. The sample size in this study is 110 reports from 22 food and beverage sub-sector companies listed on the IDX in 2022-2023. Purposive sampling is used as the sampling determination technique with certain criteria, and multiple regression analysis is used. Data analysis is conducted with the aid of SPSS software version 27. The research results show that partially only the Leverage variable has no effect, while the Profitability and Financial Distress variables have an impact on Tax Avoidance. Simultaneously, Profitability, Leverage, and Financial Distress affect Tax Avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2019-2023. These findings provide input for investors and corporate management in strategic decision-making.